Stress Intensity Factor for a Crack in a Strip - Hashim, Mohammad Hafiz (Universiti Teknologi PETRONAS, 2010)
Stress intensity factor is used in fracture mechanics to more accurately predict the stress state near the crack tip caused by remote load or residual stress. Stress intensity factor characterizes the crack-tip condition in a linear elastic material. In this project, the stress intensity factor at the crack tip for several crack geometry in finite strip will be determined by using finite element method. ANSYS software will be used to model and analyse the crack geometry to determine the stress intensity factor. The results obtained from ANSYS will be compared with the solutions available in the literature. From the comparison the accuracy of the ANSYS results can be determined.